Association of Electronic Health Record Use With Quality of Care and Outcomes in Heart Failure: An Analysis of Get With The Guidelines—Heart Failure. Issue 7 (30th March 2018) - Selvaraj, Senthil; Fonarow, Gregg C.; Sheng, Shubin; Matsouaka, Roland A.; DeVore, Adam D.; Heidenreich, Paul A.; Hernandez, Adrian F.; Yancy, Clyde W.; Bhatt, Deepak L.
Abstract : Background: Adoption of electronic health record (EHR) systems has increased significantly across the nation. Whether EHR use has translated into improved quality of care and outcomes in heart failure (HF) is not well studied. Methods and Results: We examined participants from the Get With The Guidelines—HF registry who were admitted with HF in 2008 (N=21 222), using various degrees of EHR implementation (no EHR, partial EHR, and full EHR). We performed multivariable logistic regression to determine the relation between EHR status and several in‐hospital quality metrics and outcomes. In a substudy of Medicare participants (N=8421), we assessed the relation between EHR status and rates of 30‐day mortality, readmission, and a composite outcome. In the cohort, the mean age was 71±15 years, 49% were women, and 64% were white. The mean ejection fraction was 39±17%. Participants were admitted to hospitals with no EHR (N=1484), partial EHR (N=13 473), and full EHR (N=6265). There was no association between EHR status and several quality metrics (aside from β blocker at discharge) or in‐hospital outcomes on multivariable adjusted logistic regression ( P >0.05 for all comparisons). In the Medicare cohort, there was no association between EHR status and 30‐day mortality, readmission, or the combined outcome. Conclusions: In a large registry of hospitalized patients with HF, there was no association between degrees of EHR implementation and several quality metrics and 30‐day postdischarge death or readmission. Our results suggest that EHR may not be sufficient to improve HF quality or related outcomes.